Kriteria Guru Pendidikan Pancasila dan Kewarganegaraan yang Profesional Berdasarkan Kemampuan Interpersonal Society 5.0 - Kurniawan, Bekti Galih; Virgiyanti, Diska Fatima; Marsudi, Kenlies Era Rosalina; Purbasari, Verbena Ayuning; Wiranata, Irawan Hadi (Universitas Nusantara PGRI Kediri, 2023)
The role of the teacher nowadays is not only to provide content-based conceptual knowledge but also provide knowledge about how to communicate with others. In teaching today’s generation, teachers require some special expertise. Education and training of the next generation to cope with change has become a challenge for educators as well as parents. This study aims to examine the characteristics of professional Civics teachers. There are several components that can be used as research references in formulating the characteristics of professional Civics teachers. However, the authors focus on one main component that will be studied in this study, namely interpersonal skills. A good relationship between students and teachers will have an impact on the success of learning in the classroom. This study used literature study. It is done by collecting data from books and journals that are relevant to the research study. After these data are obtained, the authors take journals or books as the main reference in formulating the characteristics of professional Civics teachers. In addition, the authors only focus on research sources that include interpersonal skills of Civics teachers. The results to be achieved in this study are to obtain several characteristics regarding Civics teachers which emphasize the teachers’ interpersonal skills. It is expected that after these characteristics are formulated, they will contribute to increasing the professionalism of Civics teachers in 5.0 societys.